Pengaruh Struktur Kepemilikan Institusional, Profitabilitas, dan Kebijakan CSR terhadap Konservatisme Akuntansi - Mustikasari, Rany; Sebrina, Nurzi (Universitas Negeri Padang, 2025)
In the turbulent years of 2020–2022, this study looks into the factors that influence accounting conservatism in state- owned companies (SOEs) listed on the Indonesia Stock Exchange (IDX). We examine the effects of institutional ownership structure, profitability, and corporate social responsibility (CSR) on accounting conservatism, using a sample of thirty businesses. Our results indicate that CSR and institutional ownership structures have a substantial impact on accounting conservatism. This implies that shifts in institutional ownership may have an impact on accounting procedures and may result in a preference for more cautious reporting techniques. But there was no discernible link between profitability and accounting conservatism, suggesting that profitability may not have a major influence on accounting procedures in emergency situations. These findings highlight how crucial it is to take into consideration non-financial aspects of SOE accounting processes, such as institutional ownership and CSR guidelines. This study also emphasizes the need for future investigation to better understand the causal links between these factors, investigate cross-sector or cross-national comparisons, and look at the effects of accounting conservatism on company performance. By shedding light on the variables impacting accounting conservatism in SOEs, this study adds to the body of knowledge already in existence. This enhances our comprehension of accounting practices in the Indonesian setting and has important ramifications for practitioners and policymakers.